Observation and assessment - Bohart, Holly; Procopio, Rossella (National Association for the Education of Young Children, 2018)
The debate surrounding testing and accountability in early childhood education continues, but one thing is universally agreed upon: effective observation and assessment of young children's learning are critical to supporting their development. Educators balance what they know about child development with observation and assessment approaches that both inform and improve the curriculum. This foundational resource for all educators of children from birth through third grade explores What observation and assessment are, why to use them, and how; Ways to integrate documentation, observation, and assessment into the daily routine ; Practices that are culturally and linguistically responsive ; Ways to engage families in observation and assessment processes ; How to effectively share children's learning with families, administrators, and others ; Find inspiration to intentionally develop and implement meaningful, developmentally appropriate observation and assessment practices to build responsive, joyful classrooms
Keywords: předškolní výchova; pedagogická evaluace; preschool children; educational evaluation; metodické příručky; methodological manuals